2013
DOI: 10.1089/ees.2013.0133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Moisture on Soil Gas Vapor Concentration for Vapor Intrusion

Abstract: Mathematical models have been widely used in analyzing the effects of various environmental factors in the vapor intrusion process. Soil moisture content is one of the key factors determining the subsurface vapor concentration profile. This manuscript considers the effects of soil moisture profiles on the soil gas vapor concentration away from any surface capping by buildings or pavement. The ''open field'' soil gas vapor concentration profile is observed to be sensitive to the soil moisture distribution. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Again, in uniform soil, the contaminant vapor profile does not depend upon soil diffusivity in any case. On the other hand, previous studies [36-37] have shown that the c ss profile is sensitive to the vertical moisture content variation in the soil. This includes a critical role of the capillary fringe above the groundwater, which acts as a very significant vapor diffusion barrier.…”
Section: Resultsmentioning
confidence: 89%
“…Again, in uniform soil, the contaminant vapor profile does not depend upon soil diffusivity in any case. On the other hand, previous studies [36-37] have shown that the c ss profile is sensitive to the vertical moisture content variation in the soil. This includes a critical role of the capillary fringe above the groundwater, which acts as a very significant vapor diffusion barrier.…”
Section: Resultsmentioning
confidence: 89%
“…This observation also supports the observations reported herein where soil moisture is thought to have retarded VOC transport, trapping higher concentrations beneath highly resistive soil layers. Modeling efforts by Shen et al 2012, 2013a, 2013b, and Moradi et al 2015 also emphasize the importance of soil moisture when evaluating vapor intrusion exposure risks.…”
Section: Resultsmentioning
confidence: 99%
“…The development, validation and applications of the 3-D finite element model examined here were already presented in former studies [1820, 2833]. In the present study, the model is applied only in a steady-state mode for non-degradable contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…The open ground surface is taken to be at atmospheric reference pressure and is a sink of zero contaminant concentration. A negative pressure of -5 Pa and a contaminant flux equation is assigned at the crack, the same as in the former studies [2833]. The detailed parameters are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation